O-003 Improving selection of patients for endovascular treatment of acute ischemic stroke: external validation of a clinical decision tool in data from the hermes collaboration. (22nd July 2018) - Venema, E; Mulder, M; Roozenbeek, B; Brown, S; Majoie, C; Demchuk, A; Muir, K; Dávalos, A; Mitchell, P; Bracard, S; Hill, M; White, P; et al.
Abstract : Background: Benefit of endovascular treatment (EVT) varies between individual patients with acute ischemic stroke. The MR PREDICTS decision tool, previously developed in the MR CLEAN trial, predicts outcome with and without EVT based on baseline patient characteristics. We externally validated this model with data from recent EVT trials. Methods: Individual patient data was derived from the six other randomized controlled trials within the HERMES collaboration (ESCAPE, REVASCAT, SWIFT-PRIME, EXTEND-IA, THRACE and PISTE). Outcome of the ordinal logistic regression model was the modified Rankin Scale (mRS) at 90 days after stroke. Discriminative performance was measured with the c-statistic, which ranges from 0.5 to 1.0. Model coefficients were updated after calibration. Results: We included 1243 patients (633 assigned to EVT, 610 assigned to control). The observed probability of functional independence (defined as mRS 0–2) was higher than predicted for treated patients (35% vs 26%) and controls (54% vs 40%), but the observed treatment benefit was comparable. The c-statistic was 0.67 (95% confidence interval (CI) 0.65–0.69) for the ordinal mRS and 0.73 (95% CI 0.70–0.76) for functional independence, similar to previous performance. figure 1 shows a screenshot of the decision tool for use in clinical practice. Conclusion: MR PREDICTS predicted outcome in a large heterogeneous trial population with discriminative value comparable to other well-known prediction tools. The updated model might be used to support clinical judgment in selection of patients for EVT. Disclosures: E. Venema: None. M. Mulder: None. B. Roozenbeek: None. S. Brown: 2; C; Medtronic. C. Majoie: 1; C; Stryker. A. Demchuk: 1; C; Covidien (Medtronic). 6; C; Covidien (Medtronic). K. Muir: 1; C; Medtronic, Codman, Stroke Association, National Institute of Health Research (NIHR) Health Technology Assessment programme. 2; C; Medtronic. A. Dávalos: 2; C; Medtronic Neurovascular. P. Mitchell: 1; C; Covidien (Medtronic), Codman Johnson and Johnson, Medtronic, Stryker. 2; C; Codman Johnson and Johnson. S. Bracard: None. M. Hill: 1; C; Covidien (Medtronic), Heart and Stroke Foundation, Alberta Innovates Health Solutions, Alberta Health Services. 4; C; Calgary Scientific Incorporated. 6; C; Merck, Hoff mann-La Roche Canada ltd. P. White: 1; C; Medtronic, Codman, Stroke Association, National Institute of Health Research (NIHR) Health Technology Assessment programme. 6; C; Microvention Terumo, Codman. B. Campbell: 1; C; National Health and Medical Research Council of Australia, Royal Australasian College of Physicians, Royal Melbourne Hospital Foundation, National Heart Foundation, National Stroke Foundation of Australia, Covidien (Medtronic). F. Guillemin: None. J. Saver: 1; C; Medtronic, Stryker. 2; C; Medtronic/Covidien, Stryker, Neuravi, BrainsGate, Pfizer, Squibb, Boehringer Ingelheim (prevention only), ZZ Biotech, St. Jude Medical, Genentech. 4; C; Cognition Medical. T. Jovin: 2; C; Codman Neurovascular, Stryker, Neuravi, Medtronic. 4; C; Blockade, Silk Road. M. Goyal: 1; C; Medtronic, Stryker. 6; C; Medtronic, Stryker, Microvention, GE Healthcare. A. van der Lugt: 1; C; Dutch Heart Foundation, Dutch Brain Foundation, Stryker, Medtronic, Penumbra. 2; C; Stryker. D. Dippel: 1; C; Dutch Heart Foundation, Dutch Brain Foundation, AngioCare BV, Medtronic/Covidien/EV3, MEDAC Gmbh/LAMEPRO, Penumbra Inc, Stryker, Top Medical/Concentric. 2; C; Stryker, Bracco Imaging. H. Lingsma: None.